Klinikkodizes als Korrektiv im ärztlichen Alltag?: Eine Reflexion zur Bedeutungorganisations ethischer Aspekte im Umgangmit der Ökonomisierung des Medizinsystems - Mehlis, Katja; Woydack, Lena; Winkler, Eva C. (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2020)
Background Economic considerations play an ever-increasing role in the decisions and actions of physicians, at times compromising the doctor-patient relationship and the quality of treatment. A reflection on an appropriate form of economization in the medical system therefore seems to be necessary. Objectives This article examines the conditions under which moral standards can be effective in daily clinical practice. Materials and methods Strategies against the scarcity of resources are evaluated using ethical criteria. Organizational ethics approaches are discussed as a possible solution. Results Economic considerations are desirable if they increase efficiency in the healthcare system. However, rationing for purely cost reasons or delivering services to increase profit are ethically questionable motives. In addition to individual care decisions, cost decisions need to be transparently weighed at the institutional and health policy levels. Through this higher-level approach, carers will be better able to focus on the core of medical treatment which is the patient's well-being. Conclusions Codes of conduct such as the DGIM (German Society of Internal Medicine) Clinic Codex can be useful ethical guidelines for patient care if they are institutionally implemented and actually used in the institution.